Use-Oriented Business Models and Flexibility in Industrial Product-Service Systems - Richter, A.; Sadek, T.; Steven, M.; Welp, E. G. (Cranfield University Press, 2009)
Today’s corporate environments are characterized by growing dynamics and uncertainties. Here, flexibility gains importance as a critical success factor. This is especially true for long-term customer-supplier relationships. As a solution to the mentioned uncertainties connected with such a business relationship, one can think of flexible systems. The contribution at hand focuses on contracts to control for customer-supplier relationships. By reallocating property rights in use-oriented business models it is possible to distribute incentives and risks to better balance the interests of customers and suppliers. Our contribution points out the importance of flexibility and describes the opportunity to detect the optimal degree of flexibility of an IPS².
Organised by: Cranfield University
Keywords: Use-oriented business models; Industrial Product-Service Systems; incomplete contracts; flexibility